2021
DOI: 10.1021/acs.est.0c05274
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Kinetics of Antibiotic Resistance Gene mecA of Methicillin-Resistant Staphylococcus aureus (MRSA) during Water Disinfection with Chlorine, Ozone, and Ultraviolet Light

Abstract: Degradation kinetics of antibiotic resistance genes (ARGs) by free available chlorine (FAC), ozone (O3), and UV254 light (UV) were investigated in phosphate buffered solutions at pH 7 using a chromosomal ARG (mecA) of methicillin-resistant Staphylococcus aureus (MRSA). For FAC, the degradation rates of extracellular mecA (extra-mecA) were accelerated with increasing FAC exposure, which could be explained by a two-step FAC reaction model. The degradation of extra-mecA by O3 followed second-order reaction kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 70 publications
10
60
0
Order By: Relevance
“…By comparing these results with the reports on changes in sewage flora following O 3 treatment [ 57 , 58 ], it is observed that the changes in the bacterial community structure composition are almost similar for O 3 and O 3 -based AOP treatment. The overall results suggest the importance of introducing advanced wastewater treatment for removal of AMRB and AMRGs, although some of them are not completely removed [ 103 , 104 , 105 ]. This seems reasonable considering the existence of multiple microorganisms [ 103 , 106 , 107 ] and AMRGs [ 108 , 109 , 110 , 111 ] in wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing these results with the reports on changes in sewage flora following O 3 treatment [ 57 , 58 ], it is observed that the changes in the bacterial community structure composition are almost similar for O 3 and O 3 -based AOP treatment. The overall results suggest the importance of introducing advanced wastewater treatment for removal of AMRB and AMRGs, although some of them are not completely removed [ 103 , 104 , 105 ]. This seems reasonable considering the existence of multiple microorganisms [ 103 , 106 , 107 ] and AMRGs [ 108 , 109 , 110 , 111 ] in wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, recent literature points out to the spread and selection of ARB and ARGs after the application of traditional technologies such as Chlorine, ozonation and UV-C irradiation/oxidant ( Jin et al, 2020 ; Kirchner et al, 2020 ; Lee et al, 2021 ; Moreira et al, 2021 ; Sharma et al, 2019 ). In addition, ozonation and UV-C irradiated processes are energy intensive and costly, which may hinder their application in developing countries.…”
Section: Resultsmentioning
confidence: 98%
“…Researchers have developed several traditional and emerging wastewater disinfection technologies to inactivate pathogenic microorganisms in wastewater (Figure ). These technologies can be divided into light-based disinfection and non-light-based disinfection, and some have received extensive research attention. The role of traditional WWTPs is generally to effectively remove impurities in sewage, including organic matters, nitrogen, phosphorus, and metals.…”
Section: Advances In Water Disinfection Technologies In Removing Arb ...mentioning
confidence: 99%